The Effect of Puncture Sites of Portal Vein in TIPS with ePTFE-Covered Stents on Postoperative Long-Term Clinical Efficacy - Si-liang Chen; Peng Hu; Zhi-peng Lin; Jian-bo Zhao (Gastroenterology Research and Practice)
Purpose. To evaluate the effect of puncture sites of the portal vein in transjugular intrahepatic portosystemic shunt (TIPS) on long-term clinical efficacy. Methods. A retrospective review was performed, including consecutive 171 patients who underwent TIPS with ePTFE-covered stents. All patients were divided into 3 groups according to the puncture site of the portal vein: intrahepatic bifurcation of the portal vein (group A, n=88), right branch of the portal vein (group B, n=48), and left branch of the portal vein (group C, n=35). The Kaplan-Meier analysis was performed to assess the effect of different puncture sites on primary patency, the incidence of hepatic encephalopathy (HE), and survival. Results. The primary restenosis rate was 29.8% (51/171). The total HE rate was 31.6% (54/171). The cumulative death rate was 19.3% (33/171). The Kaplan-Meier analysis showed that group C versus group A, group C versus group B, and group A versus group B were significantly different on the primary restenosis rate, respectively (χ2 = 11.49, P=0.001; χ2 = 4.54, P=0.033; and χ2 = 4.12, P=0.046), and group C is better than the other two groups. What is more, group C versus group A and group C versus group B were significantly different on the incidence of HE, respectively (χ2 = 8.07, P=0.004; χ2 = 9.44, P=0.002), and group C is better than the other two groups. There was no significant difference on survival. Conclusion. Choosing the left branch of the portal vein as the puncture site to create the shunt in TIPS with ePTFE-covered stents may decrease the incident of primary restenosis and HE significantly.